LAURENCE MOON BARDET BIEDL SYNDROME WITH ANAEMIA - Asif, Mariam; Aziz, Tariq; Altaf, Samer; Sattar, Rukhsana Abdul (Journal of Ayub Medical College Abbottabad, 2014)
Laurence Moon Bardet Biedl Syndrome is a rare genetic disorder. Consanguineous marriage is usually the common cause. Principal features of Bardet Biedl Syndrome are red cone dystrophy, obesity, polydactyl, hypogonadism and renal anomalies. The diagnosis was overlooked in our patient until he came in our hospital. We here report an infrequent case of autosomal recessive disorder with Anaemia. Keywords: Congenital Syndrome, Polydactyly, Bardet Biedl, Laurence Moon Syndrome